Monetary Policy and Inequality under Household Heterogeneityand Incomplete Markets - Villarreal, Francisco Gabriel (Pontificia Universidad Católica del Perú, 2022)
Motivated by the empirical evidence of the effects of unanticipated nominal interest rate increases on the evolution of household inequality in Mexico, which highlight the importance of insurance mechanisms to deal with idiosyncratic risks, the paper uses a Heterogeneous Agent New Keynesian model to analyze the relationship between monetary policy and household inequality. The model is able to capture the main features that characterise both the business cycle dynamics, as well as the distribution of income and wealth. Results indicate that heterogeneity affects the transmission of monetary policy, and that the design of monetary policy has important distributive effects.
Keywords: Heterogeneous Agents; Incomplete Markets; Mexico; https://purl.org/pe-repo/ocde/ford#5.02.01